Evaluation of an online tool about the expected course of disease for glioblastoma patients—A qualitative study. Issue 5 (4th May 2022) - van Diest, Eva; Oldenmenger, Wendy H; Eland, Marit; Taal, Walter
Abstract: Background: Patients with glioblastoma have a short life-expectancy, with median survival rates of 9 to 12 months. Providing information about the expected course of the disease can be complicated. Therefore, an online tool has been developed. The objective of this tool is to better inform patients and proxies, and decrease their uncertainties and improve their quality of life. This study aims to gather experiences of an initial cohort of patient-proxy dyads, to identify if the tool meets the previously mentioned objectives. Methods: This is a qualitative study based on thematic analysis. Interviews were conducted with 15 patient-proxy dyads. For these interviews, a combined method of think-aloud sessions and semi-structured interviews were used. Audiotapes of these interviews were transcribed verbatim and thematically analyzed. Results: The analysis revealed four major themes, namely, unmet information needs, improvement possibilities, effects of the tool and clinical implementation. Participants indicated that this tool could decrease uncertainties and increase their perceived quality of life. Also, they often mentioned that it could have a positive effect on the efficiency and quality of consultations. Conclusion: Participants considered this tool to be useful and effective in decreasing uncertainties for both patients with glioblastoma and their proxies. Moreover, participants brought up that this tool could positively influence the efficiency and quality of consultations. This could lead to more patient participation and empowerment, and could therefore enhance shared decision making and timely advanced care planning.